The Effect Of Profitability, Company Size, Leverage, And Liquidity On Tax Avoidance - Jihan Kasrina (Universitas Muhammadiyah Makassar, 2022)
This study aims to test and provide empirical evidence to prove that profitability, company size, leverage, and liquidity simultaneously or jointly have a significant effect on tax avoidance in the consumer good industry sector listed on the IDX from 2017 to 2020. This research method using quantitative data. Information analysis used in this research is descriptive statistical analysis, coefficient of determination test, f test, and t test. The procedure used is e-views version 12. This sampling method uses non-random sampling and purposive sampling methods. Based on the purposive sampling method, a sample of 10 companies was obtained. Profitability and leverage have an effect on tax avoidance in the consumer good industry sector from 2017 to 2020. Company size and liquidity have no effect on tax avoidance in the consumer good industry sector from 2017 to 2020.